Measuring electro-osmotic drag coefficients in PFSA membranes without any diffusion assumption. (20th September 2019) - Sellin, R.C.; Mozet, K.; Ménage, A.; Dillet, J.; Didierjean, S.; Maranzana, G.
Absrtract: An original set-up derived from the now standard hydrogen pump set-up is presented. The system enables isolation of the electro-osmosis as the lone macroscopic mass transport phenomenon, by minimizing or suppressing other external gradients, keeping the total pressure as the unique adjustment macroscopic parameter. The Electro-Osmotic Drag (EOD) coefficient was determined using 4 Nafion™ MEA (XL, 115, 117, 1110) as material, for temperature values in the 50–80 °C range, relative humidity (RH) values in the 30–90% range and current densities ranging from 1.2 up to 1000 mA cm −2 . Pure Nafion™membranes exhibit the same behaviours with EOD coefficients between 0.8 and 1 and which do not depend on the current density or RH. Nafion™ XL based MEA show a singular behaviour with an EOD coefficient sometime as low as 0.4 and which depends on the RH. Highlights: The electro-osmotic drag coefficient in PFSA membranes is measured without any diffusion assumptions. The Electro-Osmotic Drag coefficient was determined using 4 Nafion™ MEA (XL, 115, 117, 1110). Pure Nafion™ membranes exhibit the same behaviours with EOD coefficients between 0.8 and 1. Nafion™ XL based MEA show a singular behaviour with an EOD coefficient sometime as low as 0.4 and which depends on the RH.